Organizational Engineering In The 4.O Globalization Era In Islamic Educational Institutions - Refi Syahputra; Suryadi, Agus; Sanawi, Fahrul; Mesiono, Mesiono (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2023)
Industrial globalization, which is now characterized by 4.0, forces people to keep up with its rapid pace, therefore organizational studies must also align equipment in the form of mobile, marketing facilities, and no less importantly it needs to be operationalized so that elements are fulfilled and utilized through potential and professionalism in each work effectiveness that has been structured. The data used is qualitative. In each study, references and literacy explorations are appropriate for the object of study. its nature is to analyze and even try to synthesize findings, in the form of data, with the methods used through reduction and cross-checking of data, which have relevance. Then present the data, and conclude and check the results of the research continues in the research process. The findings in this research library include: 1) Organization is the work of each unit that shares common goals with a leader who is responsible for embodying the process and goals of the organization as a whole. 2) Organizational engineering is constructive renewal or innovation, which adapts to market and customer (society) demands in aligning the challenges of the globalization era so that organizational programs become effective and efficient. 3) The era of globalization 4.0 demands proficiency in the use and use of technology. Completion of various tasks, and increasing the competence of employees or subordinates, to make it easier for leaders to evaluate and reduce each work result. Therefore the development of the skills and competencies of people in the organization is a necessity. It is no exception in educational organizations, all education administrators must adapt to technological advances, as well as teachers who play a very important role as agents of transformation to strengthen human resources following the demands of the era of industrial globalization era 4.0. 4) The era of globalization 4.0 is the advancement of technological media so that job demands are fast and easy, minimizing time, and reducing effort. In implementing the 4.0 industrial revolution era, both from human capital, structural capital and collaborative capital with social connections, so that input, output and outcomes can be aligned.